Islam, Religious Moderation, and Digital Political Polarization: Religious Authority and Social Cohesion in the Age of Social Media - Bukhari Bukhari; Bastiar Bastiar; Muhammad Hatta; Iswandi Iswandi; Muhammad Diah (Program Pascasarjana IAIN Langsa, 2025)
The rapid expansion of digital technology has significantly reshaped religious expression and political engagement in Indonesia. Social media platforms have evolved beyond communication tools into arenas of ideological contestation, identity formation, and religiously framed political mobilization. This article examines the intersection of Islam, religious moderation, and digital political polarization through a socio-legal and digital humanities approach. Using qualitative methods based on literature review and digital discourse analysis, the study explores academic scholarship, state policies, and contemporary social media dynamics within the Indonesian context. The findings indicate that social media algorithms contribute to the formation of echo chambers and identity fragmentation, intensifying religiously infused political polarization. In such environments, religion is often instrumentalized for electoral purposes, generating potential social harm (mafsadah) and weakening social cohesion. Nevertheless, Islamic teachings provide a strong normative foundation for balance and justice through the principles of wasathiyah (moderation) and maqaṣid al-shariʿah (objectives of Islamic law), which emphasize the protection of faith, life, intellect, lineage, and property. This study argues that religious moderation must be reconstructed as an adaptive epistemological and cultural movement responsive to algorithmic logic. Strengthening value-based digital literacy, revitalizing scholarly religious authority, and fostering multi-stakeholder collaboration are essential strategies for sustaining social harmony amid digital disruption.